2023
DOI: 10.3390/ijms242417253
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnogalacturonan I with β-(1,4)-Galactan Side Chains as an Ever-Present Component of Tertiary Cell Wall of Plant Fibers

Tatyana Chernova,
Polina Mikshina,
Anna Petrova
et al.

Abstract: The cellulose-enriched tertiary cell walls present in many plant fibers have specific composition, architecture, machinery of formation, and function. To better understand the mechanisms underlying their mode of action and to reveal the peculiarities of fibers from different plant species, it is necessary to more deeply characterize the major components. Next to overwhelming cellulose, rhamnogalacturonan I (RG-I) is considered to be the key polymer of the tertiary cell wall; however, it has been isolated and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…To further investigate these varied results, we stained sections with 2% Toluidine Blue, and found that only the outer S-layers stained blue, while the G-layer was clear ( Fig. 3B,C ), indicating the G-layer is devoid of lignin, corroborating negative results with Phloroglucinol-HCl from (Chernova et al ., 2023). Lastly, analyzing unstained sections under UV fluorescence revealed signal in the outer S-layers and the innermost G-layer (the “Gn-layer” (Roach et al ., 2011; Goudenhooft, Bourmaud and Baley, 2019), but not the main body of the G-layer ( Fig.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…To further investigate these varied results, we stained sections with 2% Toluidine Blue, and found that only the outer S-layers stained blue, while the G-layer was clear ( Fig. 3B,C ), indicating the G-layer is devoid of lignin, corroborating negative results with Phloroglucinol-HCl from (Chernova et al ., 2023). Lastly, analyzing unstained sections under UV fluorescence revealed signal in the outer S-layers and the innermost G-layer (the “Gn-layer” (Roach et al ., 2011; Goudenhooft, Bourmaud and Baley, 2019), but not the main body of the G-layer ( Fig.…”
Section: Resultssupporting
confidence: 72%
“…Many vines have highly modified stem anatomies, including wholesale reorganization of the vascular tissues (Angyalossy, Pace and Lima, 2014; Cunha Neto, 2023), but common bean stems have a typical eustele and regular secondary growth. Therefore, the only clear anatomical candidate related to climbing in this species are the G-fibers; their presence has been previously reported (Chery et al 2021; Chernova et al, 2023). In young internodes, G-fibers first appear via differentiation of existing pericyclic fibers ( Fig.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations